OVERPRODUCTION OF MERCURIC REDUCTASE FROM MERCURY-RESISTANT BACTERIA KLEBSIELLA PNEUMONIAE ISOLATE A1.1.1 - Fatimawali, Fatimawali; Kepel, Billy; Tallei, Trina Ekawati (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
Mercury is a highly toxic compound in human. It can, however, be detoxified by mercuric reductase (MerA) protein derived from mercury resistant bacteria. This study aims to obtaine MerA protein by transforming merA gene into Escherichia coli BL21. Nucleotide sequence of merA gene of mercury resistant bacteria Klebsiella pneumoniae isolates A111, optimized by using gene program designers (www.dna20/com) then commercially synthesized and cloned in pET32b expression plasmid vector. Plasmid was transformed into Escherichia coli BL21 to produce MerA protein recombinant, induced with isopropyl-β-D-thiogalactopyranoside (IPTG). MerA proteins were analyzed by 10% sodium dodecyl sulphate poly acrylamide gel electrophoresis (SDS PAGE). The result showed that MerA protein with 60kDa was detected on SDS PAGE. The obtained MerA protein can be used in further research for the enzymatic detoxification of inorganic mercury.Key words: mercuric reductase, merA gene, MerA protein, Escherichia coli BL21